Sphingolipid Mediators of Myocardial Pathology - Anna Kovilakath; L. Ashley Cowart (The Korean Society of Lipid and Atherosclerosis, 2020)
Cardiomyopathy is the leading cause of mortality worldwide. While the causes of cardiomyopathy continue to be elucidated, current evidence suggests that aberrant bioactive lipid signaling plays a crucial role as a component of cardiac pathophysiology. Sphingolipids have been implicated in the pathophysiology of cardiovascular disease, as they regulate numerous cellular processes that occur in primary and secondary cardiomyopathies. Experimental evidence gathered over the last few decades from both in vitro and in vivo model systems indicates that inhibitors of sphingolipid synthesis attenuate a variety of cardiomyopathic symptoms. In this review, we focus on various cardiomyopathies in which sphingolipids have been implicated and the potential therapeutic benefits that could be gained by targeting sphingolipid metabolism.